Holistic Islamic Education: Assessing the Impact of Integrative Curricula on Moral and Spiritual Development in Secondary Schools - Saepudin, Aep (GoAcademica Research & Publishing, 2024)
Holistic Islamic education aims to nurture the intellectual, moral, and spiritual dimensions of students, providing a comprehensive framework for personal development. This study assesses the impact of integrative curricula on the moral and spiritual development of students in secondary schools. By incorporating both religious and secular subjects into a cohesive learning experience, integrative curricula seek to create a balanced educational environment that fosters overall growth. This research employs a mixed-methods approach, combining quantitative surveys and qualitative interviews to evaluate the effectiveness of these curricula. The findings reveal significant improvements in students' moral reasoning, ethical behavior, and spiritual awareness, highlighting the importance of a holistic approach to education. The study also identifies key factors that contribute to the success of integrative curricula, including teacher training, curriculum design, and school culture. The implications of this research extend to educational policy and practice, offering valuable insights for educators and policymakers aiming to enhance the moral and spiritual development of students in Islamic secondary schools.